2022
DOI: 10.3390/ijms23041995
|View full text |Cite
|
Sign up to set email alerts
|

How to Cope with the Challenges of Environmental Stresses in the Era of Global Climate Change: An Update on ROS Stave off in Plants

Abstract: With the advent of human civilization and anthropogenic activities in the shade of urbanization and global climate change, plants are exposed to a complex set of abiotic stresses. These stresses affect plants’ growth, development, and yield and cause enormous crop losses worldwide. In this alarming scenario of global climate conditions, plants respond to such stresses through a highly balanced and finely tuned interaction between signaling molecules. The abiotic stresses initiate the quick release of reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 235 publications
(281 reference statements)
1
32
0
Order By: Relevance
“…Consistently, in this study, H 2 O 2 levels and O 2 contents were lower while SOD and CAT activities were higher in transgenic Arabidopsis than WT Arabidopsis under heat stress treatments, indicating that increased SOD and CAT activities resulted from ZmNAC074 overexpression in transgenic Arabidopsis is associated with heat stress tolerance through ROS-mediated stress responsive signaling pathway. Further, APXs and GPXs can protect cells from stressinduced oxidative damage and play a key role in plant development and growth (Bela et al, 2015;Li et al, 2019;Singh et al, 2022). In this study, the significantly up-regulated expression of AtAPX1-8 and AtGPX1-8 in transgenic Arabidopsis suggested that ZmNAC074 may enhance the ability of antioxidants to scavenge excessive ROS by upregulating these antioxidant enzyme genes, thus enhancing the ability to resist heat stress.…”
Section: Overexpression Of Zmnac074 Plays a Pivotal Role In Regulatin...mentioning
confidence: 54%
See 1 more Smart Citation
“…Consistently, in this study, H 2 O 2 levels and O 2 contents were lower while SOD and CAT activities were higher in transgenic Arabidopsis than WT Arabidopsis under heat stress treatments, indicating that increased SOD and CAT activities resulted from ZmNAC074 overexpression in transgenic Arabidopsis is associated with heat stress tolerance through ROS-mediated stress responsive signaling pathway. Further, APXs and GPXs can protect cells from stressinduced oxidative damage and play a key role in plant development and growth (Bela et al, 2015;Li et al, 2019;Singh et al, 2022). In this study, the significantly up-regulated expression of AtAPX1-8 and AtGPX1-8 in transgenic Arabidopsis suggested that ZmNAC074 may enhance the ability of antioxidants to scavenge excessive ROS by upregulating these antioxidant enzyme genes, thus enhancing the ability to resist heat stress.…”
Section: Overexpression Of Zmnac074 Plays a Pivotal Role In Regulatin...mentioning
confidence: 54%
“…Further, APXs and GPXs can protect cells from stress-induced oxidative damage and play a key role in plant development and growth ( Bela et al., 2015 ; Li et al., 2019 ; Singh et al., 2022 ). In this study, the significantly up-regulated expression of AtAPX1-8 and AtGPX1-8 in transgenic Arabidopsis suggested that ZmNAC074 may enhance the ability of antioxidants to scavenge excessive ROS by up-regulating these antioxidant enzyme genes, thus enhancing the ability to resist heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Plants naturally increase the production of soluble sugar and proline content in the cytosol and other organelles to cope with the reverse effect of salt toxicity that causes superfluous osmotic stress [ 41 ]. In our study, an increase in proline and soluble sugar content was observed in M. oblongifolia plants exposed to salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggested that GPXs can protect cells from stress-induced oxidative damages and function as a vital component of growth and development in plants ( Bela et al, 2015 ). Moreover, the accumulation of ROS is regulated by a complex antioxidant scavenging system, including GRX, SOD, APX, etc., that function as antioxidants and allow the transmission of oxidative signals ( Singh et al, 2022 ). Therefore, these data suggested that increased the activity of some key antioxidant enzymes and reduced heat-induced H 2 O 2 accumulation, thus enhancing stress resistance of the transgenic plants.…”
Section: Discussionmentioning
confidence: 99%